2018
DOI: 10.3390/nano8010027
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reorientation of Graphene Platelets (GPLs) on Young’s Modulus of Polymer Composites under Bi-Axial Stretching

Abstract: Effects of bi-axial stretching induced reorientation of graphene platelets (GPLs) on the Young’s modulus of GPL/polymer composites is studied by Mori-Tanaka micromechanics model. The dispersion state of the GPLs in polymer matrix is captured by an orientation distribution function (ODF), in which two Euler angles are used to identify the orientation of the GPLs. Compared to uni-axial stretching, the increase of the stretching strain in the second direction enhances the re-alignment of GPL fillers in this direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 60 publications
0
9
0
Order By: Relevance
“…Applications range from adding graphene into polymer matrices to develop high performance multifunctional composites to super capacitors [ 6 ]. Studies have demonstrated that a small amount of graphene added into polymers can improve the overall mechanical and physical properties without reducing the beneficial attributes of the polymers [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For example, Rafiee et al [ 17 ] demonstrated that the Young’s modulus of epoxy nanocomposites can be increased by 31% by adding 0.1 wt % graphene nanoplatelet (GNP).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Applications range from adding graphene into polymer matrices to develop high performance multifunctional composites to super capacitors [ 6 ]. Studies have demonstrated that a small amount of graphene added into polymers can improve the overall mechanical and physical properties without reducing the beneficial attributes of the polymers [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 ]. For example, Rafiee et al [ 17 ] demonstrated that the Young’s modulus of epoxy nanocomposites can be increased by 31% by adding 0.1 wt % graphene nanoplatelet (GNP).…”
Section: Introductionmentioning
confidence: 99%
“…Compared to pure polymer, an increase of up to 121% in thermal conductivity was observed by Kim et al for GNP-reinforced polymer composites [ 18 ]. More work on evidencing the reinforcing effects of graphene on mechanical, thermal performance, and functionality of composite materials and structures can also be found in [ 12 , 13 , 14 , 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…The molecular dynamics (MDs) simulation developed by Sun et al [24][25][26] and Rahman et al [27][28][29][30] exhibited significant increases in the mechanical properties of GRPCs. The micromechanics modeling work [31][32][33][34] also indicated graphene fillers' prominent enhancement on the mechanical properties of GRPCs. More work on mechanical properties can be found in [35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 87%
“…Considerable work, including theoretical and experimental work [4][5][6], has demonstrated Polymer composites enhanced by graphene possess both excellent mechanical properties and impressive electrical and dielectric properties. For example, extensive theoretical and experimental work has demonstrated the mechanical performances of these composites can be remarkably enhanced by adding graphene fillers with low concentration [15][16][17][18][19][20][21]. At the same time, graphene can also substantially improve the dielectric properties of these composites.…”
Section: Introductionmentioning
confidence: 99%